Debt and Economic Growth - Zouhaier, Hadhek; Fatma, Mrad (International Journal of Economics and Financial Issues, 2014)
This paper aims to study the effect of debt on economic growth of 19 developing countries over the period 1990-2011, through the use of a dynamic panel data model. The second part of this paper involves an empirical study of the effect that debt have on the contribution of investment to economic growth. The main statements issued from these two empirical tests stipulate a negative effect of the total external debt to GDP and external debt as a percentage of GNI ratio on economic growth and a negative interaction between these two debt’ measures and investment. Keywords: debt; investment; interaction; economic growth; dynamic panel. JEL Classifications: C23; O43; O47